DESIGN OF A FUZZY CONTROLLER FOR A HEATING FURNACE SYSTEM - To, Nguyen-Nhut-Huy; Pham, Quoc-Huy; Le, Anh-Quoc; Doan, Minh-Tu; Pham, Minh-Tri; Tran, Ngoc-Huy; Nguyen, Hoang-Thien-Phuc; Tran, Thanh-Tu; Phan, Minh-Nhat; Nguyen, Phuc-Loc; Dao, Duy-Anh; Nguyen, Thai-Bao; Le, Thi-Hong-Lam (Asosiasi Peneliti Sriwijaya, 2025)
In thermal process control, conventional methods like PID often struggle to cope with nonlinearities, time delays, and external disturbances. This study presents the design and implementation of a Mamdani-type fuzzy logic controller for temperature regulation in furnace systems. Unlike traditional controllers, fuzzy logic offers flexibility, robustness, and does not require an accurate mathematical model. The proposed controller uses two input variables—temperature error and its rate of change—and one output variable to adjust the TRIAC firing angle, controlling the system's power input. Through MATLAB simulation and hardware implementation with LM35 sensors and TRIAC modules, the fuzzy system demonstrates rapid response, no overshoot, and stable operation across varying setpoints (50°C, 70°C, 90°C). Comparative results highlight the superior performance of fuzzy control over conventional PID, especially in systems with nonlinear behavior and dynamic characteristics. The findings confirm that fuzzy logic is a practical and efficient solution for real-time temperature control applications, offering high adaptability without manual parameter tuning.